2018
DOI: 10.1103/physrevlett.121.037201
|View full text |Cite
|
Sign up to set email alerts
|

Spin-to-Charge Conversion in Bi Films and Bi/Ag Bilayers

Abstract: Thermally injected pure spin current phenomena have been investigated in Bi/Y_{3}Fe_{5}O_{12} and Bi/Ag/Y_{3}Fe_{5}O_{12} structures at room temperature. We show that although pure spin current has been injected into the Bi layer and the Bi/Ag bilayer, there is little detectable signal of spin-to-charge conversion, except the distinctive Nernst signal from the Bi layer, in sharp contrast to the inverse Rashba-Edelstein effect claimed in these systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 46 publications
1
23
1
Order By: Relevance
“…Nernst effect (ONE) [36,37], that could significantly influence the observations made in harmonic Hall measurements, especially for semiconducting spin Hall materials such as the topological insulators.…”
Section: Figmentioning
confidence: 99%
“…Nernst effect (ONE) [36,37], that could significantly influence the observations made in harmonic Hall measurements, especially for semiconducting spin Hall materials such as the topological insulators.…”
Section: Figmentioning
confidence: 99%
“…3 a resistance proportional to B ext and the out-of-plane thermal gradient. Spintronic devices containing Bi and Bi-based alloys often exhibit a large ONE due to their low thermal conductivity and large Nernst coefficient [53]. In these systems, the ONE can play an important role for properly quantifying the SOTs [54].…”
Section: Dots) In This Plotmentioning
confidence: 99%
“…Despite the efforts to realize efficient spin conversion in Bi, long-term controversy remains because the reported spin Hall angle of Bi depends strongly on the measuring techniques used and the sample structures [20][21][22][23][24][25] and the magnitude is much smaller than those of Pt [5], b-Ta [26] and b-W [27], which contradicts the theoretical prediction that the SOI of Bi should be quite large. In fact, the recent study by Yue et al using the spin Seebeck effect claimed a negligible ISHE in rhombohedral (111) Bi grown on yttrium-iron-garnet (YIG) [23]. Meanwhile, studies on spin conversion in Bi film using dynamical spin pumping reported a wide variety of sizable spin Hall angles (−0.071~+0.02) [20,21].…”
mentioning
confidence: 94%